Learning for Whom? A Critical Analysis of University Students’ Motivational Orientation in the Context of Higher Education Commercialization - Karunia Kalifah Wijaya; Muhammad Royyan Masdaudi; Nanda Febrianita Handayani (Universitas Katolik Soegijapranata, 2025)
Higher education in Indonesia is undergoing commercialization, shifting its role from a public right to a market commodity. This condition influences students’ learning motivation, which is now more driven by economic pressures and labor market demands than by intrinsic drives. This study aims to examine how students interpret their learning motivation. A phenomenological qualitative approach was employed, involving ten students from various universities in Yogyakarta. Data were collected through semi-structured interviews and analyzed using thematic analysis to explore students’ subjective meanings regarding learning motivation amid educational commercialization. The study reveals that students’ motivational orientation is dynamic, shaped by the tension between internal drives and external pressures. Students experience a shift from outcome-oriented (extrinsic) motivation toward more reflective and meaningful (intrinsic) motivation, although this process is often hindered by rigid institutional structures, heavy financial burdens, and the market logic that dictates the direction of education. The pressure to meet labor market expectations and academic achievements also pushes students to adopt pragmatic strategies, often at the expense of critical thinking, collective solidarity, and autonomous learning.